Bank management & financial services - Rose, Peter S.; Hudgins, Sylvia Conway (Boston : McGraw-Hill/Irwin, 2010)
Helps students master established management principles and to confront the perplexing issues of risk, regulation, technology, and competition that bankers and other financial-service managers see as their greatest challenges for the present and future. This title offers students many of the key trends and changes in the financial-services sector.
Includes bibliographical references and index.
oif 19/05/14
Loan
Keywords: Financial institutions; Bank management; Financial services industry; Banks and banking, International